Blockade of insulin receptor substrate-1 inhibits corneal lymphangiogenesis - Hos, Deniz; Regenfuss, Birgit; Bock, Felix; Onderka, Jasmine; Cursiefen, Claus (Investigative Ophthalmology & Visual Science, 2011)
To analyze whether insulin receptor substrate (IRS-1) is involved in lymphatic vessel development and whether IRS-1 blockade can inhibit lymphangiogenesis in vivo.The impact of IRS-1 blockade by GS-101 (Aganirsen), an antisense oligonucleotide against IRS-1, on lymphatic endothelial cell (LEC) proliferation was assessed by ELISA. Furthermore, the effect of IRS-1 blockade on prolymphangiogenic growth factor expression by LECs and macrophages (peritoneal exudate cells) was tested by real-time PCR. The mouse model of inflammatory corneal neovascularization was used to analyze the effect of IRS-1 blockade in vivo: after corneal suture placement, mice were treated with GS-101 eye drops (twice daily afterwards for 1 week, 5 ?L per drop; 50, 100, or 200 ?M). Afterward, corneal wholemounts were prepared and stained for blood and lymphatic vessels.Blockade of IRS-1 by GS-101 inhibited LEC proliferation dose dependently. GS-101 led to decreased VEGF-A expression levels in LECs, whereas VEGF-C, VEGF-D, and VEGFR3 showed no significant change. In macrophages, VEGF-A expression levels were also inhibited by IRS-1 blockade. Additionally, GS-101 strongly inhibited macrophage-derived VEGF-C, VEGF-D, and VEGFR3 expression. In vivo, corneal hemangiogenesis was significantly inhibited when used at a concentration of 200 ?M (by 17%; P < 0.01). Corneal lymphangiogenesis was significantly inhibited when used at a dose of 100 ?M (by 21%; P < 0.01), and the highest used dose (200 ?M) showed an even stronger inhibition (by 28%; P < 0.001).Blockade of IRS-1 inhibits not only hemangiogenesis but also lymphangiogenesis. To the authors' knowledge, this is the first evidence that IRS-1 is involved in the molecular pathway leading to lymphangiogenesis.
EVALuna2:21053